2013
DOI: 10.1111/ppl.12077
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of β‐expansin gene GmEXPB2 improves phosphorus efficiency in soybean

Abstract: Soybean (Glycine max) is an important oil crop in agricultural production, but low phosphorus (P) availability limits soybean growth and production. Expansin is a family of plant cell wall proteins and involved in a variety of physiological processes, including cell division and enlargement, root growth and leaf development. To test the potential effects of expansins on crop production, we have developed soybean transgenic plants overexpressing a soybean β-expansin gene GmEXPB2, which was significantly induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 51 publications
1
47
0
1
Order By: Relevance
“…Four types of cis-acting elements, light responsive elements, hormone responsive elements, environmental stress-related elements, and development related elements, were found to be apparently abundant for the NtEXPs. In plants, the expression of expansins are regulated by both internal and external factors, resulting in their involvement in a variety of developmental processes, such as seed germination , fruit growth and/or ripening (Rose et al 1997;Brummell et al 1999;Ishimaru et al 2007), as well as in nutrient uptake and efficiency (Zhou et al 2014), and stress tolerance Zhao et al 2011;Lü et al 2013), which are conjured to be regulated by the corresponding cis-acting elements they contain. Plant hormones can regulate the expression of expansin genes and the regulation of expansin activity by plant hormones is well documented (Zhao et al 2012;Li et al 2014;Lu et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Four types of cis-acting elements, light responsive elements, hormone responsive elements, environmental stress-related elements, and development related elements, were found to be apparently abundant for the NtEXPs. In plants, the expression of expansins are regulated by both internal and external factors, resulting in their involvement in a variety of developmental processes, such as seed germination , fruit growth and/or ripening (Rose et al 1997;Brummell et al 1999;Ishimaru et al 2007), as well as in nutrient uptake and efficiency (Zhou et al 2014), and stress tolerance Zhao et al 2011;Lü et al 2013), which are conjured to be regulated by the corresponding cis-acting elements they contain. Plant hormones can regulate the expression of expansin genes and the regulation of expansin activity by plant hormones is well documented (Zhao et al 2012;Li et al 2014;Lu et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of plant architecture by expansins to adapt to certain external environmental changes, such as drought, heat, low phosphorus (P), is also well studied (Cosgrove 2015;Lu et al 2016). Some examples include the wheat (Triticum aestivum) TaEXPB23, Poa pratens PpEXPA1, soybean GmEXPB2 and rose (Rosa hybrida) RhEXPA4, the transgenic plants with which gained tolerance to drought (Li et al , 2013, tolerance to heat (Xu et al 2014), improved P efficiency Zhou et al 2014) and tolerance to drought and salt (Lü et al 2013;Yan et al 2014), respectively. In addition, we found that for many cis-elements two or more copies located at adjacent sites, which might enhance the effects of their binding to trans-acting factors such as transcription factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore effects of GmEXPB2 on nodule organogenesis, soybean transgenic composites and whole transgenic plants were generated according to Guo et al (2011) and Zhou et al (2014), respectively. The transgenic composite plants included GmEXPB2 OX, suppression (RNAi), and empty vector (CK) lines.…”
Section: Characterization Of Nodule Organogenesis Using Soybean Wholementioning
confidence: 99%
“…These are changes that are observed in response to drought condition , Zhou et al, 2014. In 2003, Lee et al demonstrated the role of GmEXP1 in cell wall expansion at the developing site of the tobacco plant root.…”
Section: Introductionmentioning
confidence: 99%